A simple and easily implemented design for an ultra-broadband variable phase compensator. (13th February 2015) - Xu, Shixiang; Chen, Wenting; Cai, Yi; Lu, Xiaowei; Chen, Hongyi; Zheng, Guoliang; Li, Jingzhen
Abstract: We propose a novel design for a variable phase compensator (VPC) to improve bandwidth by minimizing the birefringent phase retardation (BPR) dispersion. Especially at the near-zero BPR point, the VPC has an extremely broad bandwidth. The VPC is based on only two kinds of birefringent crystals, and all its included components can be manufactured almost without need of dimension tolerance, which greatly simplifies its manufacture. According to our calculations, the VPC can keep its relative residual BPR within 2.4% with an ADP/KDP material combination, much smaller than that of the traditional quartz VPC for the tunable BPR from −180° to 180° in the spectral zone from 0.6 to 1.0 μ m. This kind of VPC is suitable for accurately manipulating the polarization of broadband light pulses.